Environmental footprints of beef cattle production in the United States. (February 2019) - Rotz, C. Alan; Asem-Hiablie, Senorpe; Place, Sara; Thoma, Greg
Abstract: The environmental impacts of beef cattle production and their effects on the overall sustainability of beef have become a national and international concern. Our objective was to quantify important environmental impacts of beef cattle production in the United States. Surveys and visits of farms, ranches and feedlots were conducted throughout seven regions (Northeast, Southeast, Midwest, Northern Plains, Southern Plains, Northwest and Southwest) to determine common practices and characteristics of cattle production. These data along with other information sources were used to create about 150 representative production systems throughout the country, which were simulated with the Integrated Farm System Model using local soil and climate data. The simulations quantified the performance and environmental impacts of beef cattle production systems for each region. A farm-gate life cycle assessment was used to quantify resource use and emissions for all production systems including traditional beef breeds and cull animals from the dairy industry. Regional and national totals were determined as the sum of the production system outputs multiplied by the number of cattle represented by each simulated system. The average annual greenhouse gas and reactive N emissions associated with beef cattle production over the past five years were determined to be 243 ± 26 Tg carbon dioxide equivalents (CO2 e) and 1760 ± 136 Gg N, respectively. Total fossil energy use was found to be 569 ± 53 PJ and blue water consumption was 23.2 ± 3.5 TL. Environmental intensities expressed per kg of carcass weight produced were 21.3 ± 2.3 kg CO2 e, 155 ± 12 g N, 50.0 ± 4.7 MJ, and 2034 ± 309 L, respectively. These farm-gate values are being combined with post farm-gate sources of packing, processing, distribution, retail, consumption and waste handling to produce a full life cycle assessment of U.S. beef. This study is the most detailed, yet comprehensive, study conducted to date to provide baseline measures for the sustainability of U.S. beef. Highlights: Life cycle environmental impacts of U.S. beef cattle production were determined. Annual carbon emission was 243 ± 26 Tg CO2 e (21.3 ± 2.3 kg CO2 e/kg carcass weight). Annual fossil energy use was 569 ± 53 PJ (50.0 ± 4.7 MJ/kg carcass weight). Blue water consumption was 23.2 ± 3.5 TL (2034 ± 309 L/kg carcass weight). Reactive nitrogen loss was 1760 ± 136 Gg N (155 ± 12 g N/kg carcass weight).